Zimbabwe : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix analyzes recent trends in poverty and social indicators for Zimbabwe. It discusses land reform, agricultural policies, and the outcomes. The paper presents background information on the evolution of inflation and money aggregates in Zimbabwe. It analyzes the demand of money since the late 1990s, and discusses factors that can lead to diverging paths of inflation and money growth in the short term. The paper also analyzes Zimbabwe's export performance in recent years, and identifies the factors that could improve export performance, from both a quantitative and qualitative perspective.